2013
DOI: 10.1007/s12016-013-8373-z
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Opioids on the Lung

Abstract: The term opioid refers to a broad class of medications that are used most frequently for their analgesic effects. Along with this effect, they also produce euphoria, and it is for this reason that they have been used illicitly, as well as medicinally, for thousands of years. While the most well-known complications of opioid use and misuse include respiratory and central nervous system depression, there are many other toxicities that have been associated with these drugs. Many complications can occur with multi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
32
1
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(37 citation statements)
references
References 82 publications
1
32
1
3
Order By: Relevance
“…Excluding mitragynine, the medical examiner concluded that all other substances in the blood were at levels that would be unlikely to contribute to the cause of death. The pulmonary congestion and edema identified through autopsy, though not specific, supported this conclusion; these findings are typically observed in deaths resulting from opioid use . With no prior attempts or outward signs of suicide noted, the medical examiner classified the decedent's manner of death as an “accident.” When compared with other fatal cases involving mitragynine toxicity, the elevated concentrations of mitragynine in the current case report are some of the highest levels reported to date .…”
Section: Resultsmentioning
confidence: 92%
“…Excluding mitragynine, the medical examiner concluded that all other substances in the blood were at levels that would be unlikely to contribute to the cause of death. The pulmonary congestion and edema identified through autopsy, though not specific, supported this conclusion; these findings are typically observed in deaths resulting from opioid use . With no prior attempts or outward signs of suicide noted, the medical examiner classified the decedent's manner of death as an “accident.” When compared with other fatal cases involving mitragynine toxicity, the elevated concentrations of mitragynine in the current case report are some of the highest levels reported to date .…”
Section: Resultsmentioning
confidence: 92%
“…The pulmonary infiltrates are not due to infection (pneumonia), can be bilateral or unilateral and resolve within 48 h [19]. Multiple recent reports have documented unilateral pulmonary infiltrate associated with a high leukocyte count following heroin overdose [19][20][21][22]. Both resolve spontaneously within 48 h and are not associated with infection [19][20][21][22].…”
Section: Discussionmentioning
confidence: 99%
“…Multiple recent reports have documented unilateral pulmonary infiltrate associated with a high leukocyte count following heroin overdose [19][20][21][22]. Both resolve spontaneously within 48 h and are not associated with infection [19][20][21][22]. In the 25-year-old male, after normal physical examination on day 2, the internist obtained a chest X-ray to document the disappearance of infiltrates.…”
Section: Discussionmentioning
confidence: 99%
“…Another entity that can occur in association with opioid abuse is noncardiogenic pulmonary edema (NCPE) (56,57). In one cohort of patients who presented with symptoms of opioid overdose, NCPE was found in 10% of these patients, with a male predominance.…”
Section: Noncardiogenic Pulmonary Edema and Acute Lung Injurymentioning
confidence: 99%
“…In one cohort of patients who presented with symptoms of opioid overdose, NCPE was found in 10% of these patients, with a male predominance. The pulmonary edema is most often caused by the opioid itself and is seen in association with the use of different µ-receptor agonists, including heroin and buprenorphine (56,57). It is worth mentioning that in some cases, NCPE has also been attributed to naloxone use rather than the opioid itself (58).…”
Section: Noncardiogenic Pulmonary Edema and Acute Lung Injurymentioning
confidence: 99%